A novel role for poly(C) binding proteins in programmed ribosomal frameshifting - Napthine, S.; Treffers, E. E.; Bell, S.; Goodfellow, I.; Fang, Ying; Firth, A. E.; Snijder, E. J.; Brierley, I. (My University, 2016)
Translational control through programmed ribosomal frameshifting (PRF) is exploited widely by viruses and increasingly documented in cellular genes. Frameshifting is induced by mRNA secondary structures that compromise ribosome fidelity during decoding of a heptanucleotide 'slippery' sequence. The nsp2 PRF signal of porcine reproductive and respiratory syndrome virus is distinctive in directing both -2 and -1 PRF and in its requirement for a trans-acting protein factor, the viral replicase subunit nsp1 beta. Here we show that the the trans-activation of frameshifting is carried out by a protein complex composed of nsp1 beta and a cellular poly(C) binding protein (PCBP). From the results of in vitro translation and electrophoretic mobility shift assays, we demonstrate that a PCBP/nsp1 beta complex binds to a C-rich sequence downstream of the slippery sequence and here mimics the activity of a structured mRNA stimulator of PRF. This is the first description of a role for a trans-acting cellular protein in PRF. The discovery broadens the repertoire of activities associated with poly(C) binding proteins and prototypes a new class of virus-host interactions.
Citation: Napthine, S., Treffers, E. E., Bell, S., Goodfellow, I., Fang, Y., Firth, A. E., . . . Brierley, I. (2016). A novel role for poly(C) binding proteins in programmed ribosomal frameshifting. Nucleic Acids Research, 44(12), 5491-5503. doi:10.1093/nar/gkw480
Keywords: Kh Domain Proteins; Messenger-Rna; Gene-Expression; Poly(C)-Binding; Proteins; Translation Initiation